Care burden dimensions of informal caregivers having patients with bipolar disorder (challenges and alternatives) (qualitative study) - Mehdi Kargar; Seyed Aliakbar Faghihi; Mahin Nazari (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Taking care of patients with bipolar disorder (BD) makes critical challenges for their informal caregivers (ICGs) and forces them to tolerate considerable burden. This qualitative study explored the dimensions of ICGs' care burden (CB) based on their own experiences and the patients' therapists. MATERIALS AND METHODS: This is a qualitative study which was conducted based on conventional content analysis through semistructured and in-depth interviews. Purposive sampling was used to select the participants including 13 ICGs and 14 therapists (2 psychiatrists, 10 psychiatric nurses, and 2 clinical psychologists). Interviews were audiotaped, transcribed verbatim, and analyzed using Graneheim's 2004 principles. RESULTS: Qualitative analyses yielded three major themes: "challenges associated with the nature of BD," "challenges related to the ICGs," and "challenges related to interventions." The categories of the first theme entailed "individual-oriented characteristics of BD" and "social-oriented characteristics of BD." The categories of the second theme consisted of "social stigma," "psychiatric problems and helplessness of ICGs," "financial costs related to providing cares," and "insufficient self-efficacy of ICGs in cares provision." The categories of the last theme included "educational interventions" and "organizational interventions." CONCLUSIONS: This study showed that the burden of ICGs have individual, social, and organizational aspects. Every one of them impacts the severity of their burden remarkably. The depth of the therapists' experiences has a significant role in designing the interventions to reduce this burden. The present investigation emphasized the constitution of a comprehensive framework related to all factors affecting burden in a developing country.